Bismuthanides and bismuthanediides: synthesis and structural characterization of [R2Bi]− and [(RBi)12Na21]3− salts with bulky Silyl substituents - Linti, Gerald W.; Köstler, Wolfgang; Pritzkow, Hans (European journal of inorganic chemistry, 2002)
The reaction of bismuth trihalides with the bulky alkali metal silanides [(THF)3LiSi(SiMe3)3] and [(THF)2NaSi(CMe3)3] affords the cyclotetrabismuthanes (RBi)41 and 3, the alkali metal bismuthanides [Li(THF)4][Bi{Si(SiMe3)3}2]...